Effect of rubber mats and perforation in the lying area on claw and limb lesions of fattening pigs. (15th January 2018) - Falke, A.; Friedli, K.; Gygax, L.; Wechsler, B.; Sidler, X.; Weber, R.
Abstract : Claw and leg lesions are frequently observed in finishing pigs and are likely to compromise their welfare. Providing softer than the usual concrete flooring may reduce both the frequency and severity of these lesions. Therefore, this study evaluated the influence of rubber mats and floor perforation in the lying area on claw and leg health of finishing pigs. A total of 240 Swiss Large White finishing pigs from on average 24.9 kg until 102.3 kg were used in four batches, with six groups of 10 animals per batch. The six experimental pens initially measured 1.85×3.55 m and were enlarged after 6 weeks to 1.85×5.25 m. In all pens, one third of the floor space was built as a defecating area consisting of a concrete floor with 15% perforation. The remaining two thirds of the pen were designed as a lying area whose floor quality differed between the pens. It either consisted of concrete elements or was covered with rubber mats, and perforation of both floor types was either 0%, 5% or 10%. All individuals were scored for claw and leg lesions at the beginning, in the middle and at the end of the 12-week fattening period. Lesions were summarised in scores based on the results of a principal component analysis. The influence on lesion scores of floor material, amount of perforation in the lying area, assessment time, and sex was examined using mixed-models. The total claw lesion score and the total limb lesion score as well as the claw angle increased from the beginning to the end of the fattening period. The values for both scores were slightly lower for animals kept on rubber mats compared with animals kept on concrete floor. There was no effect of the percentage of perforation on the examined outcome variables. In conclusion, our results indicate that rubber mats in the lying area bring about improvements in some aspects of claw and leg health in fattening pigs, whereas there is no effect of floor perforation.